Immunomodulatory effects and mechanisms of distraction osteogenesis - Shude Yang; Ning Wang; Yutong Ma; Shuaichen Guo; Shu Guo; Hongchen Sun (Nature Publishing Group, 2022)
Abstract Distraction osteogenesis (DO) is widely used for bone tissue engineering technology. Immune regulations play important roles in the process of DO like other bone regeneration mechanisms. Compared with others, the immune regulation processes of DO have their distinct features. In this review, we summarized the immune-related events including changes in and effects of immune cells, immune-related cytokines, and signaling pathways at different periods in the process of DO. We aim to elucidated our understanding and unknowns about the immunomodulatory role of DO. The goal of this is to use the known knowledge to further modify existing methods of DO, and to develop novel DO strategies in our unknown areas through more detailed studies of the work we have done.